2014
DOI: 10.1007/s12041-014-0319-6
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of dormancy and cooking quality traits in direct-seeded indica rice

Abstract: Association analysis was applied to a panel of accessions of Assam rice (indica) using 98 SSR markers for dormancy-related traits and cooking quality. Analysis of population structure revealed 10 subgroups in the population. The mean r(2) and D' value for all intrachromosomal loci pairs was 0.24 and 0.51, respectively. Linkage disequilibrium between linked markers decreased with distance. Marker-trait associations were investigated using the unified mixed-model approach, considering both population structure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The results revealed that marker i.e., RM22565 on chromosome 8 exhibited significant (P<0.0001) association with germination (%) at five days after harvesting. Similar results for significant association of seed dormancy and germination at five days after harvesting with RM106 on chromosome 2 were reported by Rathi et al (2014). Several groups have attempted to identify the genomic regions/QTLs linked to dormancy and found some QTLs on different chromosomes of rice.…”
Section: Resultssupporting
confidence: 80%
“…The results revealed that marker i.e., RM22565 on chromosome 8 exhibited significant (P<0.0001) association with germination (%) at five days after harvesting. Similar results for significant association of seed dormancy and germination at five days after harvesting with RM106 on chromosome 2 were reported by Rathi et al (2014). Several groups have attempted to identify the genomic regions/QTLs linked to dormancy and found some QTLs on different chromosomes of rice.…”
Section: Resultssupporting
confidence: 80%
“…Rathi et al . 86 have reported ten subgroups in a population of 100 indica rice using 98 SSR markers. Anandan et al .…”
Section: Discussionmentioning
confidence: 99%
“…e principal components 1 and 2 accounted for 48.11 and 20.85% of the total variation, respectively. Based on the average-environment coordination (AEC), the genotypes NERICA 14 (8), ART3-7-L9P8-1-B-B-1 (9), and NERICA 8 (7) appeared as the highest yielding genotypes among which NERICA 8 and ART3-7-L9P8-1-B-B-1 were the most stable across environment. CNAX 3031-78-2-1-7, NERICA 6, and ART16-12-22-1-3-1-1-B-1-B were the lowest yielding genotypes.…”
Section: Stability and Mean Performance Across Environmentsmentioning
confidence: 99%
“…e upland rice appears as a promising sustainable crop that can contribute to cope with food security issue [6]. Development of new upland rice varieties has become a serious research interest for some Asian countries such as Vietnam [7], India [8], and China [9]. With regard to Africa, recent efforts were done by Africa Rice and their collaborators in order to develop upland rice varieties adapted to growing conditions in tropical regions.…”
Section: Introductionmentioning
confidence: 99%